Tinjauan Yuridis Wanprestasi dalam Perjanjian Sewa Lahan Pemerintah Daerah Berdasarkan Buku III KUHPer dan PP No. 27 Tahun 2014 (Studi Kasus Auning Pedagang Stadion Maulana Yusuf Serang) - Siti Safitri; Dede Agus; Rully Syahrul Mucharro (Catalist Indo Publisher, 2025)
The purpose of this study is to analyze the implementation of the land lease agreement at Maulana Yusuf Stadium in the development of traders’ auning between the Tourism and Sports Office and Basyar Alhafi, and to assess its legal consequences when reviewed from Book III of the Civil Code and Government Regulation Number 27 of 2014 concerning the Utilization of State Property. The research employs a normative juridical method using statutory, conceptual, and case approaches, supported primarily by secondary data and complemented by primary data. The analysis is carried out qualitatively. The findings show that the cooperation agreement formed between the Tourism and Sports Office and Basyar Alhafi did not comply with the required procedures because it was made without discussion or approval from the Mayor of Serang as the authorized holder of regional property management. This procedural defect renders the agreement inconsistent with applicable laws and regulations. Furthermore, the agreement cannot be canceled unilaterally because the tenant, Basyar Alhafi, rejected the cancellation. In conclusion, the dispute requires the Tourism and Sports Office to submit a lawsuit to the Serang District Court to annul the agreement and restore control over the regional property.